Oil Price Volatility, Organization Capital, and Firm Performance - Javed Bin Kamal; Mabel D. Costa; Ahsan Habib (American Business Review, 2022)
We examine the relationship between oil price volatility and firm performance, and the moderating role of organization capital on this relationship. Using U.S. firm-level data during the period of 1986-2017, our analysis reveals several key findings. Consistent with the real option theory, we find that oil price volatility negatively affects firm performance. However, this adverse effect of oil price volatility is reduced for firms with high levels of organization capital. Interestingly, this moderating effect of organization capital is more pronounced for firms with large cash holdings. Overall, our findings substantiate the idea that firms with high levels of organization capital can hedge oil price related volatilities effectively. Findings from several robustness tests support our key results.